Psychological Well-being Among Older Adults: The Role of Partnership Status - Wright, Matthew R.; Brown, Susan L. (Journal of marriage and family, 2017)
Today's older adults are increasingly unmarried. Some are in cohabiting unions, others are dating, and many remain unpartnered. Unmarried older adults are at risk of poorer well-being than married older adults, but it is unclear whether older cohabitors fare worse than or similar to their married counterparts; nor have well-being differences among cohabitors, daters, and unpartnered persons been considered. Conceptualizing marital status as a continuum of social attachment, data from Waves I and II of the National Social Life, Health, and Aging Project are used to examine how older married, cohabiting, dating, and unpartnered individuals differ across multiple indicators of psychological well-being. Among men, cohabitors appear to fare similarly to the married, and better than daters and the unpartnered. In contrast, there are few differences in psychological well-being by partnership status for women.